Effects of compulsory schooling on mortality: Evidence from Sweden - Martin Fischer; Martin Karlsson; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2013)
Theoretically, there are several reasons to expect education to have a positive effect on health and empirical research suggests that education can be an important health determinant. However, it has not yet been established whether education and health are indeed causally related, and the effects found in previous studies may be partially attributable to methodological weaknesses. Moreover, existing evidence on the education-health relationship using information of schooling reforms for identification, generally use information from fairly recent reforms implying that health outcomes are observed only over a limited time period. This paper examines the effect of education on mortality using information on a national roll-out of a reform leading to one extra year of compulsory schooling in Sweden. In 1936, the national government made a seventh school year compulsory; however, the implementation was decided at the school district level, and the reform was implemented over a period of 12 years. Taking advantage of the variation in the timing of the implementation across school districts, by using county-level proportions of reformed districts, census data and administrative mortality data, we find that the extra compulsory school year reduced mortality. In fact, the mortality reduction is discernible already before the age of 30 and then grows in magnitude until the age of 55-60.
Keywords: I12; I14; I18; I21; 330; Returns to schooling; Education Reform; Mortality